Cover Picture: Plasma Process. Polym. 4/2018. Issue 4 (16th April 2018) - Vandenbossche, Marianne; Petit, Laurène; Mathon‐Lagresle, Julie; Spano, Fabrizio; Rupper, Patrick; Bernard, Laetitia; Hegemann, Dirk
Abstract : Front Cover: Plasma polymerization was investigated on a substrate partly shielded from direct plasma exposure by an inclined static mask protecting film growth from ion bombardment and moderating diffusion processes. A lateral gradient coating was formed underneath the mask thanks to the diffusion of film‐forming species showing different reactivities, resulting in varying chemistry and wettability as well as decreasing film thickness and roughness with increasing distance from the mask/plasma edge. Further details can be found in the article by Marianne Vandenbossche et al. (e1700185 ).